Teachers’ Views on the Utility of the Teacher’s File (International Journal of Scientific Research and Management (IJSRM), 2018)
In 2010, the Department of Basic Education instructed its teachers to maintain a teacher’s file. This article reports on a research project which described teachers’ views on the utility of the teacher’s file and its relationship to skill of reflection related continuous professional teacher development (CPTD). The research described the meaning and the sense teachers attached to maintaining this file in the light of assumptions and principles of the experiential learning theory (ELT). It also probed ideas related to how the file could be improved and developed into a resource that contributes to the professional development of teachers in terms of teaching, learning and assessment (TLA). The study utilized interviews and document study as tools to collect data which were later analyzed and interpreted to arrive at the research findings and recommendations. The study found that all teachers regarded the teachers’ file as an administrative tool which had nothing to do with their own professional development. They regarded it as a management tool which was meant to monitor them. The study found that to acquire more meaning to the teacher, the file must be enhanced to include more teacher advancement related matters. In view of the teachers’ feelings that the file was purely administrative, the Department of Basic Education could review its current format and render it relevant to the professional development of the teacher. The aspects of professional development must include specific areas such as teaching, learning, assessment, classroom management and administration.